Multiomics studies with co-transformation reveal microRNAs via miRNA-TF-mRNA network participating in wood formation in Hevea brasiliensis - Chen, Jinhui; Liu, Mingming; Meng, Xiangxu; Zhang, Yuanyuan; Wang, Yue; Jiao, Nanbo; Chen, Jianmiao (Frontiers in Plant Science, 2023)
MicroRNAs (miRNAs) are small endogenous non-coding RNAs that play an important role in wood formation in plants. However, the significance of the link between miRNAs and their target transcripts in wood formation remains unclear in rubber tree (Hevea brasiliensis). In this study, we induced the formation of reaction wood by artificially bending rubber trees for 300 days and performed small RNA sequencing and transcriptome deep sequencing (RNA-seq) to describe the complement of miRNAs and their targets contributing to this process. We identified 5, 11, and 2 differentially abundant miRNAs in normal wood (NW) compared to tension wood (TW), in NW relative to opposite wood (OW), and between TW and OW, respectively. We also identified 12 novel miRNAs and 39 potential miRNA-mRNA pairs with different accumulation patterns in NW, TW, and OW. We noticed that many miRNAs targeted transcription factor genes, which were enriched in KEGG pathways associated with phenylpropanoid biosynthesis, phenylalanine metabolism, and pyruvate metabolism. Thus, miRNA-TF-mRNA network involved in wood formation via tension wood model were constructed. We validated the differential accumulation of miRNAs and their targets by RT-qPCR analysis and overexpressed miRNA in Nicotiana benthamiana with its potential target gene. These results will provide a reference for a deep exploration of growth and development in rubber tree.